Potential value of red and brown seaweed for sustainable bioethanol production - Hamouda, Ragaa A; Hussein, Mervat H; El-Naggar, Noura El-Ahmady (Bangladesh Journal of Botany, 2018)
Algae are renewable sources of feedstock for bioethanol that can be grown on non arable lands, non productive water sources and inexpensive culture systems. Red seaweed Laurencia obtusa and brown seaweeds Cystoseira compressa, Colpomenia sinuosa were analysed by determining sugar content by HPLC and converted into suitable fermentable feedstock by NaOH, H2SO4, HCl and H3PO4 at concentrations 1, 2, 3, 4 and 5% at 21°C of 20 minutes. The efficiency of hydrolysis significantly improved by 5% HCl for Laurencia obtusa at 42.84 g sugar/100 g dry biomass. Pretreatment of Cystoseira compressa and Colpomenia sinuosa with 3 and 5% H3PO4 gave higher sugar content of 30.51 and 41.34 g/100 g dry biomass, respectively. A relatively high level ethanol of 0.146 g/g dry biomass of Laurencia obtusa was produced. Results indicate that Cystoseira compressa and Laurencia obtusa can be good feedstocks for bioethanol production.